Metabolic remodelling in hypertrophied and failing myocardium: a review - Peterzan, M; Lygate, C; Neubauer, S; Rider, O (American Physiological Society, 2017)
The energy starvation hypothesis proposes that maladaptive metabolic remodelling antedates, initiates and maintains adverse contractile dysfunction in heart failure (HF). Better understanding of the cardiac metabolic phenotype and metabolic signalling could help identify the role metabolic remodelling plays within HF and conditions known to transition toward HF, including 'pathological' hypertrophy. In this review, we discuss metabolic phenotype and metabolic signalling in the contexts of pathological hypertrophy and HF. We discuss the significance of alterations in energy supply (substrate utilization, oxidative capacity and phosphotransfer) and energy sensing using observations from human and animal disease models and models of manipulated energy supply/sensing. We aim to provide ways of thinking about metabolic remodelling that centre around metabolic flexibility, capacity (reserve) and efficiency, rather than around particular substrate preferences or transcriptomic profiles. We show that maladaptive metabolic remodelling takes multiple forms across multiple energy-handling domains. We suggest that lack of metabolic flexibility and reserve (substrate, oxidative and phosphotransfer) represent a final common denominator ultimately compromising efficiency and contractile reserve in stressful contexts.